2022
DOI: 10.3389/fncel.2022.838432
|View full text |Cite
|
Sign up to set email alerts
|

Brevican and Neurocan Cleavage Products in the Cerebrospinal Fluid - Differential Occurrence in ALS, Epilepsy and Small Vessel Disease

Abstract: The neural extracellular matrix (ECM) composition shapes the neuronal microenvironment and undergoes substantial changes upon development and aging, but also due to cerebral pathologies. In search for potential biomarkers, cerebrospinal fluid (CSF) and serum concentrations of brain ECM molecules have been determined recently to assess ECM changes during neurological conditions including Alzheimer’s disease or vascular dementia. Here, we measured the levels of two signature proteoglycans of brain ECM, neurocan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 59 publications
(74 reference statements)
2
5
0
1
Order By: Relevance
“…As the biosynthesis of brevican and neurocan occurs largely in neural tissue and fragments of these proteins have been detected in CSF ( ; accessed on 1 September 2022) [ 31 ] it is of interest to analyze their concentration in the CSF of patients as a potential proxy of brain levels of these signature ECM components. In agreement with our recent study [ 32 ], we show that CSF concentrations of these proteoglycans and their major cleavage products positively correlate with the age of the patients and with Aβ1-40, an indicator for the glymphatic flux from the parenchyma to the CSF [ 33 ]. Although we did not see a group-wise difference between control and AD patients, which is in line with earlier studies from other labs [ 18 , 19 , 34 ], we found clear correlations with tau measures, NF-L, and the Aβ ratio, and—at least for brevican—also with the MMSE score.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…As the biosynthesis of brevican and neurocan occurs largely in neural tissue and fragments of these proteins have been detected in CSF ( ; accessed on 1 September 2022) [ 31 ] it is of interest to analyze their concentration in the CSF of patients as a potential proxy of brain levels of these signature ECM components. In agreement with our recent study [ 32 ], we show that CSF concentrations of these proteoglycans and their major cleavage products positively correlate with the age of the patients and with Aβ1-40, an indicator for the glymphatic flux from the parenchyma to the CSF [ 33 ]. Although we did not see a group-wise difference between control and AD patients, which is in line with earlier studies from other labs [ 18 , 19 , 34 ], we found clear correlations with tau measures, NF-L, and the Aβ ratio, and—at least for brevican—also with the MMSE score.…”
Section: Discussionsupporting
confidence: 92%
“…Commercial ELISA kits (RayBiotech Norcross, GA, USA) (ELH-BCAN-1 and ELH-NCAN-1) were used for the quantitative measurement of total brevican and neurocan in the CSF samples (dilution 1:300 for anti-brevican ELISAs and 1:10 for anti-neurocan ELISAs). ELISA measurements were essentially conducted according to the manufacturer’s instructions and to [ 32 ], with slight modifications: To compensate for sensitivity differences in ELISA batches the concentration of the recombinant calibrator protein for the standard curve was adjusted according to OD values obtained (highest standard concentrations were set to 3 ng/mL in brevican ELISAs and 25 ng/mL in neurocan ELISAs; standard dilution series: 6 × 1:2 dilution steps). HRP-streptavidin was used at concentrations of 1:200 for brevican and 1:500 for neurocan.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alterations in the expression levels of BCAN (brevican core protein isoform X2; overexpressed DEP with 2.08 FC) and NCAN (neurocan core protein isoform X2; overexpressed DEP with 4.16 FC) have been reported in epileptic patients, as in the case of focal cortical dysplasia [ 103 , 104 ]. Epilepsies with a genetic basis can manifest early in life, and both BCAN and NCAN are believed to play crucial roles in terminal differentiation during development, as well as in the adult nervous system during postnatal development.…”
Section: Discussionmentioning
confidence: 99%
“…Both forms may be cleaved. As shown in Figure 2e, our blots show high molecular weight soluble brevican as well as a previously described approximately 50-60 kDa metalloprotease generated cleavage fragment (Seidenbecher et al ., 1995; Hussler et al ., 2022). This proteolytic fragment is significantly increased in APOE3/3 as compared to APOE4/4 CSF samples ( p = 0.0039, Student’s t test).…”
Section: Resultsmentioning
confidence: 99%